Enhancing understanding and improving academic performance - Zakaria, Nurul Aimi (Universiti Teknologi MARA, Perak, 2025)
3 Jan 2025 – Two series workshop, held on the 29th November 2025 and 3 January 2025 was organized by Faculty of Applied Science. A total of 25 student from Diploma in Science, University of Technology MARA (UiTM) Perak Branch, Tapah Campus, participated in the workshop and each participant received module to occupy in the program. The module includes mind maps for each topic in the Modern Physics course and as well as addition question for students to try and challenges themselves.